Proceso de transición de niña a mujer: ritual de la primera menstruación, Comunidad Shawi de Nuevo Chacatán, San Juan Bautista Loreto 2023 - Rodríguez Macuyama, Nixia Nubia Loidid (2024)
The study titled "Transition process from girl to woman: Ritual of the first menstruation in the Shawi community of Nuevo Chacatán, San Juan Bautista Loreto 2023" used a qualitative approach and adopted the ethnographic method for its implementation. Key informants were identified, such as the president of the community, as well as mothers and daughters who had experienced their first menstruation. Additionally, data collection tools such as semi-structured interviews and debriefing guides were employed to gain a detailed understanding of the process of the first menstruation ritual over time. The results of the study reveal that the ritual of the first menstruation has undergone changes over time, but it is the grandmothers and mothers who continue to transmit knowledge to new generations of women, thus contributing to preserving and practicing the traditions of New Shawi women. Chacatan. Likewise, it is evident that from the moment a girl begins to menstruate, she begins her transition towards maturity, considering the ritual of passage from girl to woman or "old lady" as a form of integration into social life and the Shawi cosmological universe. The Shawi community of Nuevo Chacatán has preserved its own customs and institutions, which are at risk of disappearing due to the external influence of mestizo customs. This ritual of passage contributes to unite and strengthen traditional practices and institutions within Shawi culture and society.